Internet of Things: Architecture, Security and Cryptdb : Monomi - Ambika, G; Srivaramangai, P (International Journal of Computer Sciences and Engineering, 2025)
Cloud users demands security to their data which are stored in data repositories of cloud service provider. Thus the concept of Network Security can be applied over the cloud network, where several encryption algorithms are applied to provide integrity on the data. Such algorithms include Symmetric encryptions, Asymmetric encryptions, Hashing algorithms and Digital signatures. MONOMI is a system for securely executing analytical workloads over sensitive data on an untrusted database server. MONOMI works by encrypting the entire database and running queries over the encrypted data. CryptDB is a MySQL proxy that allows SQL aware encryption inside existing database management systems. To offer the best possible protecting while enabling the greatest computational flexibility it relies on a new concept called onions, where different layers of encryption are wrapped around each other and are only revealed as necessary. While its concept to improve database security looks fresh and interesting from an academic standpoint we wanted to examine the usability in practical application to determine if a real world productive use is desirable